Manajemen Bandwidth dan Kontrol Akses Jaringan Menggunakan Mikrotik Pada Lembaga PAUD: Studi Kasus RA Hasanah - Hasanah, Hanisha; Salsabila, Khalisha Haya; Gemintang, Rayhan Enggal; Fadillah, Muhammad Hafizh; Ramadhan, Muhammad Hatta; Juhdahu, Barun; Hidayat, Rahmat (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
Internet connection reliability is essential for facilitating administrative tasks in educational settings, including early childhood education facilities like RA Raudhoh Hasanah. The establishment is experiencing inconsistent internet service due to a lack of Wi-Fi access points and the unavailability of a bandwidth control system. This research intends to introduce a network management system utilizing MikroTik devices to address these problems. The study employs a descriptive qualitative methodology that includes five organized phases: planning, gathering data, designing the system, executing it, and conducting tests. The network architecture was constructed using a bridge topology, configured with a DHCP Server, managed bandwidth through Simple Queue, and a hotspot system that operates on vouchers via the Mikhmon interface. Testing and evaluation results demonstrate notable enhancements in internet reliability and distribution of bandwidth. Furthermore, the voucher system simplifies management of user access with improved flexibility. As a result, the implemented system has shown to be effective in enhancing administrative activities at RA Raudhoh Hasanah.